Reducing Government Expens in the Public budget using some financial engineering tools : The Republic of Iraq As a Model (Journal of Accounting and Financial Studies ( JAFS ), 2024)
government spending in the state’s public budget . The research community was the Ir     The research aims to reduce government expenditures in the state’s public budget, identify financial engineering tools in how to reduce expenditures, and demonstrate the impact of these tools in reducing aqi Ministry of Finance by relying on the actual financial data of the research sample, which is The Accounting Department for the period from 2016 to 2021, in addition to other data that strengthened the practical aspect, was obtained from the Ministry of Commerce, the two general companies for food trade and grain trade. The inductive approach and analytical description were followed, and the methods, ideas, and tools of financial engineering were used in order to find solutions to the financial problems of government financial institutions. Represented by reducing expenditures, both current and investment, in the state’s general budget. The research concluded that the use of financial engineering methods, ideas, and tools contributes to finding solutions to financial problems, which are represented by reducing budget expenditures and managing its risks well. The use of financial engineering applications, such as hedging against an increase in commodity prices, During (options contracts / American option) it contributed to reducing the prices of imported basic commodities, which in turn is reflected in the provision of larger quantities of these commodities, and that the total public expenditures in the budget are constantly rising and are directed towards operational expenditures at the expense of investment expenditures.